2022
DOI: 10.1101/2022.05.16.22275174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulmonary function among rural residents in high air pollution area in northern Thailand

Abstract: Background: Air pollution has become a serious environmental and health issue in several countries. This condition leads to respiratory diseases, particularly asthma and chronic obstructive pulmonary disease (COPD). This study aimed to determine pulmonary functions and prevalence of respiratory diseases among rural residents in an area in northern Thailand with a high concentration of air pollution. Methods: A cross-sectional study was conducted in people aged 18 years or older, living in Lamphun, Thailan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…More recent assessments have observed a potential decrease in morbidity in the last few years (Chi Htwe et al, 2023) and have concluded that 33.1% of individuals report a respiratory symptom when the PM2.5 average value is 35 μg/m 3 (2 to 128 μg/m 3 ). These individuals described their symptoms as 14.2% of runny nose; 10.2% of nasal obstruction; 9.4% of cough; 7.9% of sputum production 7.1% of allergic rhinitis and 6.3% of breathlessness and an additional 15.7% of abnormal lung function reported (Ruchiwit et al, 2022). Another earlier study found that the 5 main symptoms were 34.8% of blocked nose, 33.7% of tiredness, 32.9% of body itch, 30.7% of burning & itchy eyes and 28.7% of running nose (Wiwatanadate, 2014).…”
Section: General Symptomsmentioning
confidence: 99%
“…More recent assessments have observed a potential decrease in morbidity in the last few years (Chi Htwe et al, 2023) and have concluded that 33.1% of individuals report a respiratory symptom when the PM2.5 average value is 35 μg/m 3 (2 to 128 μg/m 3 ). These individuals described their symptoms as 14.2% of runny nose; 10.2% of nasal obstruction; 9.4% of cough; 7.9% of sputum production 7.1% of allergic rhinitis and 6.3% of breathlessness and an additional 15.7% of abnormal lung function reported (Ruchiwit et al, 2022). Another earlier study found that the 5 main symptoms were 34.8% of blocked nose, 33.7% of tiredness, 32.9% of body itch, 30.7% of burning & itchy eyes and 28.7% of running nose (Wiwatanadate, 2014).…”
Section: General Symptomsmentioning
confidence: 99%